2018
DOI: 10.3389/fneur.2018.00431
|View full text |Cite
|
Sign up to set email alerts
|

Betahistine Treatment in a Cat Model of Vestibular Pathology: Pharmacokinetic and Pharmacodynamic Approaches

Abstract: This study is a pharmacokinetic (PK) and pharmacodynamics (PD) approach using betahistine doses levels in unilateral vestibular neurectomized cats (UVN) comparable to those used in humans for treating patients with Menière's disease. The aim is to investigate for the first time oral betahistine administration (0.2 and 2 mg/kg/day) with plasma concentrations of betahistine and its major metabolite 2-pyridylacetic acid (2-PAA) (N = 9 cats), the time course of posture recovery (N = 13 cats), and the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…With respect to betahistine, both preclinical and clinical studies have suggested a wide range of potential effects. Firstly, it modulates histaminergic neurotransmission by partially agonizing the activity of the H 1 receptor, but it has, however, more potent antagonistic properties on the histamine H 3 receptor, inducing an overall increase in histamine turnover and release [25,26]. Secondly, it affects neuronal excitability and spike generation in lateral and medial vestibular nuclei.…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to betahistine, both preclinical and clinical studies have suggested a wide range of potential effects. Firstly, it modulates histaminergic neurotransmission by partially agonizing the activity of the H 1 receptor, but it has, however, more potent antagonistic properties on the histamine H 3 receptor, inducing an overall increase in histamine turnover and release [25,26]. Secondly, it affects neuronal excitability and spike generation in lateral and medial vestibular nuclei.…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
“…Ideally, drugs capable of enhancing vestibular compensation may be prescribed in order to induce an acceleration of functional recovery, especially in those patients with reduced mobility, which may prevent a successful vestibular physical rehabilitation. For this purpose, some reports indicate that betahistine [26] or Ginkgo biloba extract, an antioxidant agent with mild antiplatelet activity [35], seem to induce an acceleration of functional recovery. However, the use of betahistine in the routine treatment protocol of patients with AUV may be considered as an option, on the basis of a Cochrane review affirming that low-quality evidence suggests that in patients suffering from vertigo from different causes, there may be a positive effect of this drug in terms of reduction in vertigo symptoms [36].…”
Section: Acute Unilateral Vestibulopathy (Auv)mentioning
confidence: 99%
“…Individual treatment trials suggest that combining orally administered betahistine with the MAO-B inhibitor selegiline may enhance its efficacy: this can be understood in light of the fact that 99% of orally ingested betahistine is metabolized in the gastrointestinal tract by MAO-B/A. This approach has received support from experimental studies in animals in a model of acute unilateral vestibulopathy (21). On the whole, more randomized and controlled trials are needed to study the therapeutic effects of betahistine.…”
Section: Treatment With Betahistinementioning
confidence: 99%
“…Unilateral vestibular lesion also results in an increase in the support surface delimited by the animal’s four paws. This parameter is a good estimate of postural stability and restoration of balance (4, 8, 24, 25). When we compared the support surface area of each group between the preoperative values and the values obtained after UVN (D1-D30), we observed that the UVN-NaCl group significantly increased their support surface area the first 3 days following vestibular lesion (D1 to D3: p < 0.001) and reached pre-operative control values from D7 until D30 ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%